Long-term phosphorus fertilisation increased the diversity of the total bacterial community and the phoD phosphorus mineraliser group in pasture soils - Tan, Hao; Barret, Matthieu; Mooij, Marlies; Rice, Olivia; Morrissey, John; Dobson, Alan; Griffiths, Bryan; O'Gara, Fergal (Springer, 2013)
Fertilisers, especially nitrogen (N) and phosphorus (P) supplies, are frequently used in agricultural soil management to attain high crop yields. However, the intensive application of these chemical inputs can decrease the quality of agricultural soils and increase the probability of environmental pollution. In this study, the impact of P fertilisation on the diversity of the soil bacterial community was assessed. For this, a culture-independent approach targeting 16 rRNA and phoD genes was used on DNA extracted from pasture soils subjected to three different P fertilisation regimes for a long-term (42 years). As alkaline phosphomonoesterase (ALP) is necessary for mineralisation of organic P, an inverse relationship between the level of potential ALP activity and soil available P was expected. Indeed, a lower ALP activity was observed in soil subjected to higher chemical P fertiliser input. Analysis of the prevalence of three divergent families of ALP (PhoA, PhoD and PhoX) in metagenomic datasets revealed that PhoD is the most frequent ALP in soil samples and was selected as the most representative ALP possessed by the soil bacterial communities. Diversity of the phoD phosphorus mineraliser group, as well as the total bacterial community, was both increased in response to long-term P fertilisation. Specifically, phosphorus fertilisation decreased the relative abundance of certain taxa, including Acidobacteria and Pseudomonas fluorescens. In conclusion, this study shows that P fertilisation affects the microbial diversity of soil ecosystems, which might potentially modulate the soil biogeochemical cycle.